Edukasi Makanan Pendamping Air Susu Ibu (MP-ASI) Sebagai Upaya Peningkatan Daya Tahan Tubuh Balita Di Posyandu Desa Pematang Balam - Rismayani Rismayani; Fadillah Sari; Retno Rismawati; Dwi Hermawati; Lety Arlenti (Gayaku Publisher, 2023)
One of the efforts to improve toddler nutrition requires good nutrition in order to increase the body's resistance to infection. Complementary foods (MP-ASI) are foods and drinks that contain good nutrients and are given to infants or children aged 6–24 months to meet nutritional needs other than those met by breast milk. There are still mothers of toddlers in the Pematang Balam Village Posyandu group who do not know about the provision of good and correct complementary foods. Therefore, it is necessary to provide information to mothers related to MP-ASI. The purpose of this community service activity is to increase the knowledge of mothers with toddlers, especially those who have children aged 6–24 years, about providing good and correct complementary food. The mothers of toddlers in Pematang Balam Village are the intended audience for this activity.The method of implementation is by direct discussion. The results of the activity are that there is an increase in the knowledge of mothers of toddlers about complementary foods after monitoring and evaluating activities in collaboration with cadres and implementing the provision of complementary foods properly and correctly by these mothers.